„Coverage of Cultural Topics and Objects in Traditional Electronic (Radio and Television) And New Media” - Todorova, Irina (Media and Language, 2020)
The focus of the research is the media coverage of culture in the traditional electronic (radio and television) and the new media.It is analyzed to what extent the latter are a continuation of the former in the modern digital environment; what is the attitude of the recipients to the high level of cultural content produced by the established public broadcast media, as well as to what extent the presented content related to culture in the private electronic media is recognized as such by the respondents. The research includes the identification of the modern and preferred sources of cultural information of the respondents.
Keywords: investigation; online; offline environment; traditional; new media